Analysis of Registered Dietitian Nutritionists (RDNs) Knowledge, Attitudes, and Beliefs on Transgender Nutrition Care in Michigan - J. Ford; E. Colling; D. Hannah; S. Hand (Journal of the Academy of Nutrition and Dietetics, 2024)

Response of Cyclopia subternata to drought stress – assessment of leaf composition, proteomics and product quality - G.S. Mabizela; M. van der Rijst; M.M. Slabbert; P. Mathabe; M. Muller; D. de Beer; M. Stander; J. Colling; B. Walczak; E. Joubert; C. Bester (South African Journal of Botany, 2023)

Compressibility and structure behaviour of maruyamaite (K-tourmaline) from the Kokchetav massif at high pressure up to 20 GPa - Anna Yu. Likhacheva; S. V. Rashchenko; Kira A. Musiyachenko; Andrey V. Korsakov; Ines E. Collings; Michael Hanfland (Mineralogy and Petrology, 2019)

A temperature-sensitive allele of a putative mRNA splicing helicase down-regulates many cell wall genes and causes radial swelling in Arabidopsis thaliana - Paul A. Howles; Leigh K. Gebbie; David A. Collings; Arvind Varsani; Ronan C. Broad; Stephen Ohms; Rosemary J. Birch; Ann H. Cork; Tony Arioli; Richard E. Williamson (Plant Molecular Biology, 2016)

Identification and in silico characterisation of defective molecules associated with isolates of banana bunchy top virus - Daisy Stainton; Darren P. Martin; David A. Collings; John E. Thomas; Arvind Varsani (Archives of Virology, 2016)

EURRECA—Estimating Zinc Requirements for Deriving Dietary Reference Values - Nicola M. Lowe; Fiona C. Dykes; Anna-Louise Skinner; Sujata Patel; Marisol Warthon-Medina; Tamás Decsi; Katalin Fekete; Olga W. Souverein; Carla Dullemeijer; Adriënne E. Cavelaars; Lluis Serra-Majem; Mariela Nissensohn; et al. (Critical Reviews in Food Science and Nutrition, 2013)

EURRECA—Evidence-Based Methodology for Deriving Micronutrient Recommendations - Rosalie A. M. Dhonukshe-Rutten; Jildau Bouwman; Kerry A. Brown; Adriënne E. J. M. Cavelaars; Rachel Collings; Evangelia Grammatikaki; Lisette CPGM de Groot; Mirjana Gurinovic; Linda J. Harvey; Maria Hermoso; Rachel Hurst; Bas Kremer; et al. (Critical Reviews in Food Science and Nutrition, 2013)

Rapid serological profiling by enzyme-linked immunosorbent assay and its use as an epidemiological indicator of foot-and-mouth disease viral activity - I. E. Bergmann; E. Neitzert; V. Malirat; S. Ortiz; A. Colling; C. Snchez; E. Correa Melo (Archives of Virology, 2003)

Response of freshwater microcosm communities to nutrients, fish, and elevated temperature during winter and summer - D. McKee; D. Atkinson; S. E. Collings; J. W. Eaton; A. B. Gill; I. Harvey; K. Hatton; T. Heyes; D. Wilson; B. Moss (Limnology and Oceanography, 2003)
Under conditions of stress, shallow freshwater ecosystems can undergo a state change characterized by the rapid loss of macrophytes and subsequent dominance of phytoplankton. Elevated water temperature may promote such change. Here we report the impact of two warming regimes (continuous 3°C above ambient and 3°C above ambient during summer only), with two nutrient loadings and the presence or absence of fish, on 48 microcosm ecosystems created to mimic shallow pond environments. We found that warming did not significantly encourage phytoplankton blooms, even in combination with increased nutrients and fish. Instead, macrophyte communities remained dominant. Macrophyte‐associated invertebrates (gastropods and ostracods) increased in numbers in the warmed microcosms, potentially helping to stabilize the macrophyte communities. Nevertheless, warming produced trends in water chemistry that could be problematic. It increased phosphorus concentrations, total alkalinity, and conductivity. It decreased pH and oxygen saturation and increased the frequency of severe deoxygenation. These trends were largely independent of the other experimental treatments and support the suggestion that moderate warming has the potential to exacerbate existing eutrophication problems.

Growth dynamics and cytoskeleton organization during stem maturation and gravity-induced stem bending in Zea mays L. - David A. Collings; Heike Winter; Sarah E. Wyatt; Nina S. Allen (Planta, 1998)

Interaction between nickel and iron in the rat - Forrest H. Nielsen; Terrence R. Shuler; Thomas J. Zimmerman; Michael E. Collings; Eric O. Uthus (Biological Trace Element Research, 1979)